Research on construction and application of gene network model for form design based on consumer's preference. (October 2021) - Fan, Jiashuang; Yu, Suihuai; Yu, Mingjiu; Chu, Jianjie; Chen, Dengkai; Zhong, Daixing; Zhang, Yukun; Hu, Zhigang; Liu, Jing; Yang, Gangjun; Tian, Baozhen; Wang, Jinlei; et al.
Abstract: With developments in science and technology, product innovation is the key to enterprise performance in the competitive market. In consumer demand-oriented modern product design, effectively combining product design with the esthetic perceptions and preferences of consumers is a problem that urgently needs to be addressed. However, the traditional design method is completely dominated by designers without user participation. The purpose of this study was to give designers an impetus for restructuring and upgrading a design. A gene network design model was developed with the advantages of a gene network and neural network. This allowed the target elements of a product design to be obtained using a nonlinear network. Finally, a case study was used to show the detailed procedure of the design model. To reveal the advantages of the proposed model, it was compared with other methods such as a gene-based design method, an emotional design method, and a fuzzy Kano design method. The results showed that the proposed model was more efficient and scientific, and provided consumers with a multidimensional evaluation system to determine the optimal design schemes.